Challenges in managing a critically ill patient with decompensated Eisenmenger syndrome - Min, Xian Lim; Abdul Jabbar Ismail; Yeap Boon Tat (BMJ Publishing Group, 2022)
Eisenmenger syndrome (ES) is the most severe form of pulmonary arterial hypertension and is associated with congenital heart disease. ES itself is a challenging condition to manage, further compounded if the patient is critically ill and acutely decompensated. We share our experience of managing a critically ill adult patient with ES who presented with acute decompensation due to sepsis.